Analog circuit design art, science, and personalities - Williams, Jim, 1948-2011. (Boston : Butterworth-Heinemann, 1991)
This book is far more than just another tutorial or reference guide - it's a tour through the world of analog design, combining theory and applications with the philosophies behind the design process. Readers will learn how leading analog circuit designers approach problems and how they think about solutions to those problems. They'll also learn about the `analog way' - a broad, flexible method of thinking about analog design tasks. A comprehensive and useful guide to analog theory and applications. Covers visualizing the operation of analog circuits. Looks at how to rapidly determine workable approximations of analog circuit parameters.
pt. 1. Introduction -- pt. 2. What is analog design? -- pt. 3. The making of an analog engineer -- pt. 4. Intuitions and insights -- pt. 5. Techniques, tips, and applications.
Includes bibliographical references and index.
Keywords: Linear integrated circuits -- Design and construction; Electronic circuit design; Electronic books